Case report of the first use of a hydrogel rectal spacer for prostate cancer reirradiation via LDR brachytherapy: applications and technical notes - Lazrek, Amina; Finocchi Ghersi, Sebastiano; Petre, Adeline; Houabes, Sarah; Serre, Anne-Agathe; Gassa, Frederic; Sandt, Magali; Laude, Cecile; Roukoz, Camille; Cozzi, Salvatore (Frontiers in Oncology, 2025)
IntroductionProstate cancer remains a prevalent malignancy among men, often necessitating innovative therapeutic strategies for effective management of recurrent cases. This article examines the critical role of a biodegradable hydrogel spacer, which creates a temporary interspace between the prostate and the rectum, thus reducing radiation exposure to healthy tissues.Case descriptionWe present a case of a man with a history of intermediate-risk prostate adenocarcinoma initially treated with external beam radiotherapy in 2015. Despite initial remission, the patient experienced a rise in prostate-specific antigen (PSA) levels indicative of local recurrence in 2022. Salvage treatment with iodine-125 brachytherapy, preceded by the placement of a rectal spacer in January 2024, resulted in a significant reduction of PSA levels. The patient remains asymptomatic with no urinary or gastrointestinal complications 6 months after the salvage treatment.DiscussionThis case illustrates the complexities in managing recurrent prostate cancer and the evolving role of reirradiation strategies. Salvage iodine-125 brachytherapy with the placement of a rectal spacer provided precise radiation delivery while minimizing rectal toxicities. The significant biochemical response observed underscores the efficacy of this approach in controlling disease progression. The rectal spacer enhances treatment safety by reducing radiation exposure to adjacent tissues, highlighting its importance in reirradiation protocols. This case contributes to the growing evidence supporting the rectal spacer’s role in enhancing the safety and efficacy of salvage brachytherapy for recurrent prostate cancer.ConclusionsOur experience advocates for the integration of a hydrogel rectal spacer as a valuable tool in prostate cancer reirradiation protocols, offering a strategic approach to optimize treatment safety by minimizing rectal toxicity.